ANALISIS KINERJA KEUANGAN DALAM PERSPEKTIF RASIO LIKUIDITAS PADA KEPUTUSAN SEBELUM DAN SESUDAH RIGHT ISSUE - Irham Fahmi (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2011)
The research goal is for analysis financial performance in form company financial ratiobefore and after right issue is done in the companies that go public in Indonesia Stock Exchange toin 2008. The financial ratios as in this research are liquidity. The firm to be population in the ofresearch consists 20 firms, financial report data required in this research included in 1997-1998 ( twoyear after right issue) and financial report in 2000-2001 (two year before right issue). While tostatistic test used Wilcoxon matched-pairs signed-ranks test.As hypothesis used in this research that is a significant difference between financialperformance before and after right issue.The result, shows there is differenly significant ratio of liquidity, solvency, and profitability intwo term of the year before ( 1997-1998) and two term of the year after ( 2000 and 2001) right issue. The liquidity happened to increase having a meaning two term of the year after of this right issuecaused by company get included of it fund addition of right issue.